IDENTIFIKASI BATUAN PENYUSUN SISTEM PANAS BUMI NON-VULKANIK BANGKA TENGAH BERDASARKAN PENAMPANG 2D ANOMALI GAYA BERAT - Eri Gusnia; Tri Kusmita (JOURNAL ONLINE OF PHYSICS, 2023)
The geothermal system in the Central Bangka area is a radiogenic non-volcanic geothermal system. This geothermal system is not associated with the volcanism process. The purpose of this research is to identify the rock components of the Non-Volcanic geothermal system in the Central Bangka geothermal field based on the 2D cross section of the gravity anomaly. This research was conducted by performing spectral analysis using Fast Fourier Transform (FFT) on the complete Bouger anomaly to obtain the residual anomaly. 2D modeling of the residual anomaly was done using inverse modeling with the smoothness constraint equation. The results show that the subsurface structure of the non-volcanic geothermal system in the Central Bangka geothermal area consists of cover rock in the form of sandstone (2.38 - 2.42 gr/cm3) at a depth of 3,000 m, reservoir rock consists of granite. (2.65 - 2.66 gr/cm3) at a depth of 0 - 9,000 m and the bedrock consists of diorite (2.87 - 2.9 gr/cm3) at a depth of 2,000 - 10,000 m.